Determination of body surface and direction of crossing with motor transport wheels in forensic medical experience - Yu. A. Shamarin; Ye. V. Kalyanov; A. D. Shnayder (Бюллетень сибирской медицины, 2003)
In the article it have been systematized morphologic features allowing to define what body surface had been subjected to the crossing with motor transport wheels and the direction of crossing. Answer to this question is of great practical importance. 60 cases of determined automobile injuries (crossing a body) have been analyzed.